Systematic and casuistic approaches to the role of victims in criminal proceedings before the International Criminal Court (2009)
The scope of victims’ participation at the investigation stage of a situation and throughout case-related proceedings is today one of the critical issues before the ICC. The key provision on this matter is Article 68(3) of the Rome Statute. This provision entrusts the ICC Chambers with the discretion to determine (i) when victims can participate in ICC proceedings and (ii) the specific manner in which such participation can take place. The present article, which is written against the backdrop of the first Review Conference scheduled for next year pursuant to Article 121(1) of the Rome Statute, focuses on the systematic and casuistic approaches adopted so far by different ICC chambers in shaping, pursuant to Article 68(3) of the Statute, the role of victims at the investigation stage of a situation and in case-related proceedings.